Perception toward formative assessment literacy and practice among secondary school mathematics teachers - Aba-Wajji, Nasser Aba-Milki; Weldmeskel, Fisseha Mikre; Ayane, Zenebe Negewo (Intelektual Pustaka Media Utama, 2026)
This study investigated the perceived formative assessment literacy and practice among mathematics teachers at secondary schools to examine the impact of literacy on assessment practices. The cluster random sampling technique was employed to select sample districts, schools, and participants. A total of 64 mathematics teachers took part in the study. The measuring scales applied for data collection were the “Teacher formative assessment literacy scale and teacher formative assessment practice scale”. The data analysis was performed with SPSS 27 software to compute mean scores, standard deviations, intervals, and regression coefficients. The result showed that teachers’ literacy and practice of formative assessment are at a moderate level, but the classroom practice is more teacher-directed. Regression analysis revealed that assessment literacy significantly predicted assessment practice (β=0.67, p0.001), implying assessment literacy showed a moderately positive impact on assessment practice (R2=0.359, F(1, 62)=34.962, p0.001), The study concluded the need to improve teacher formative assessment literacy and practice levels to enhance their ability to utilize formative assessment in student teaching and learning strategies properly. The study’s implications and recommendations indicate the arrangement of intervention and on-the-job professional development training for teachers.